Designing Corporate Performance Management System Using Integrated Performance Measurement System: Case Study Hilbrew Coffee - Jonathan, Ivan; Wibisono, Dermawan (Journal of Business and Management, 2016)
Abstract.Â Company performance plays an important role in maintaining the sustainability of a company. Hilbrew Coffee, a coffee based company was establish in 2014. After 3 years running the business, the company still doesnâ€™t have PMS to measure their performance. This research use Integrated Performance Management System (IPMS) as the framework in designing the performance management system for Hilbrew Coffee.Keywords: Designing; Performance Management; IPMS; Start-up Company; Porter